The Aesthetic Authority of Sultan Hamengku Buwana X in the Creation of Traditional Dance: A Study on the Bedhaya Mintaraga at the Yogyakarta Court - Syahrial, Syahrial; Sriyadi, Sriyadi; Fahrinisa, Febika (RIRAI Publisher, 2025)
The bedhaya dance is a significant Javanese dance genre, often associated with royalty, serving as a means to showcase the majesty and authority of a monarch. Therefore, it’s customary for a Sultan, occupying the highest social status in the Yogyakarta Court, to have bedhaya dances as part of his repertoire. One way for a Sultan to acquire bedhaya dances is by commissioning the creation of new ones during his reign, as exemplified by Sultan Hamengku Buwana (HB) X’s creation of the Bedhaya Mintaraga dance. This research aims to describe the Sultan HB X’s involvement, considering his hierarchical status and aesthetic authority, in the creation process of the Bedhaya Mintaraga dance. Understanding the Sultan HB X’s significant role in determining a new bedhaya dance during his reign is crucial. This qualitative research employs an ethnochoreological approach, utilizing non-field study data sources. Findings indicate that the Sultan HB X plays a significant role as the creator, evident in the dawuh dalem (royal decree) and controlling actions he exercises. Through these decrees and controls, the Sultan HB X manifests his aesthetic authority, having the power to determine his creations within the Bedhaya Mintaraga dance, which stands as a significant addition to his reign’s cultural legacy.